Japan and the great divergence : A short guide - Francks, Penelope (Palgrave studies in economic history, 2016)
The book examines Japan's economic development within the framework of the Great Divergence, analyzing historical and institutional factors that distinguished Japan's path from that of Europe and shaped its role in the global economy